Wrocław – miasto spotkań? Wrocławskie inicjatywy wielokulturowe - Sanecka, Anna (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2016)
Wrocław is the city where besides Polish and Catholic majority many representatives of different national, ethnical and religious minorities live. Most of these minorities are active and present on city’s cultural map in a way. But is the presence and activity of these minorities enough to call Wrocław a meeting place? For last few years a debate has been held in the local media on whether the multiculturalism of the city is a fact or only a myth? Do ethnical, national and religious minorities meet in Wrocław, does majority meet them, and if so, to what extent? In this respect common activities seem to be the most interesting – not only those held within the framework of cooperation among the minorities, but also with the participation of the representatives of dominant culture. The article is aimed to present few examples the multicultural, multi-religious, multinational and multi-ethical projects held in the city of Wrocław as well as to confront them with the outcries doubting the multiculturalism of Wrocław.
Keywords: multiculturalism; Wroclaw; national minorities; ethnical minorities; religious minorities; myth of multiculturalism